Sociological analysis of a modern young family's problems - Nadezhda Afanasievna Frolova; Alexey Yurievich Cherkasov (Вестник Майкопского государственного технологического университета, 2023)
The article examines the problems that young families face today on the basis of the theoretical analysis and analysis of empirical data. The relevance of the scientific research is due, firstly, to demographic processes associated, among other things, with a high level of divorces, and secondly, the crisis of the traditional form of a family, the transformation of the system of spiritual and social values, the formation of attitudes towards egocentrism and consumerism.The purpose of the research to identify and characterize the problems of a modern young family.The object of the research is a young family, the subject is the problems of a modern young family.During the study, the method of questionnaire [n=120] and expert survey has been used. Experts from the Orlovsky Crisis Center in the city of Orel (10 people) acted as experts. The study has showed that some of the problems faced by a modern young family are objective, others are objective-subjective.The authors have identified four groups of problems of a young family: the first group consists of problems conditioned by financial situation of a family, the second - problems of a communicative nature, the third - socio-psychological problems and the fourth - problems associated with the personal characteristics of young spouses. The authors note that spiritual and moral education, which includes the formation of family values, is a basic condition for preserving not only a young family, but also the family as a social institution.